INTERNET ADDICTION AND THE LEVEL OF PSYCHOLOGICAL FATIGUE AMONG PRIMARY SCHOOL STUDENTS: AN EPIDEMIOLOGICAL ANALYSIS - Umedova M. E.; Nigmatullayeva D. J. (The Conference Hub, 2025)
Over the past decades, the widespread integration of digital technologies into the educational process has led to a sharp increase in internet use in the daily lives of primary school–aged children.